1971
DOI: 10.1111/j.1476-5381.1971.tb09946.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aminoguanidine, chlorpromazine and NSD‐1055 on gastric secretion and ulceration in the Shay rat

Abstract: Both chlorpromazine and NSD‐1055 (a non‐steroidal anti‐inflammatory drug) markedly lower the volume and acidity of gastric contents of rats subjected to pyloric ligation (Shay technique) and reduce the degree of ulceration in the stomach. On the other hand, aminoguanidine (an inhibitor of histaminase) has no effect on acid secretion or ulceration in these animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
1

Year Published

1974
1974
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
4
1
Order By: Relevance
“…With regard to pharmacological experiments, though some authors have reported that HDI inhibit gastric acid secretion in the rat [20][21][22][23] others could not confirm it [24][25][26][27]. In our experiments, HDI did not inhibit the pentagastrin-stimulated gastric acid secretion in the doses applied, but these compounds markedly potentiated and also prolonged the antisecretory effect of histamine H2-receptor antagonists in both pre-and simultaneous treatments.…”
Section: Discussioncontrasting
confidence: 70%
“…With regard to pharmacological experiments, though some authors have reported that HDI inhibit gastric acid secretion in the rat [20][21][22][23] others could not confirm it [24][25][26][27]. In our experiments, HDI did not inhibit the pentagastrin-stimulated gastric acid secretion in the doses applied, but these compounds markedly potentiated and also prolonged the antisecretory effect of histamine H2-receptor antagonists in both pre-and simultaneous treatments.…”
Section: Discussioncontrasting
confidence: 70%
“…Estimation of oxidative stress biomarkers in serum and gastric tissue Blood samples were collected in centrifuge tubes then allow clotting for serum separation. Centrifugation at 3000 rpm for 15 minutes induced clear non-hemolysed sera that used for antioxidants activity assay: catalase (CAT) [24] , superoxide dismutase (SOD) [25] as well as determination of malondialdehyde (MDA) level concentrations [26] .…”
Section: Evaluation Of Fundic Mucosal Injurymentioning
confidence: 99%
“…In rats with chronic gastric fistulae, NSD 1055 reduced the response to pentagas trin. Radwan and West (121) found that 200 mg/kg NSD 1055 intraperitoneally resulted in only a small reduction in the volume and total acidity of 16-hour Shay rats, but considerably reduced the incidence and extent of gastric ulcera tion. Becker and Sewing (14), using the anaesthetized gastric perfused rat, were only able to show inhibition of tetragastrin-stimulated gastric acid secretion with 100 mg/kg NSD 1055 when administered intravenously; when oral or intraperitoneal routes were used, tetragastrin-stimulated gastric acid secretion was poten tiated.…”
Section: Gastric Secretory Effects O F Decarboxylase Inhibitorsmentioning
confidence: 99%